The Effect of Hypnosis Breastfeeding (Hypnobreastfeeding) on Breastfeeding Self Efficacy in Postpartum Mothers at Kediri City - Rohmah, Miftakhur; Wahyuni, Candra; Mufida, Riza Tsalatsatul (STRADA : Jurnal Ilmiah Kesehatan, 2021)
The research design used was a quasy experiment with a nonequivalent control group design approach involving 40 postpartum mothers as respondents consisting of 20 treatment groups and 20 control groups, which were taken by purposive sampling. The statistical test used in this study is the Mann Whitney test. The results showed that the rest-feeding self-efficacy in the control group was mostly in the category of less than 80% (16 people), and in the treatment group mostly in the good category of 85% (17 people). The results of statistical tests using Mann Whitney obtained p-value (0.00 <0.05), which means that there is an effect of giving breastfeeding hypnosis (hypnobreastfeeding) on breastfeeding self-efficacy in postpartum mothers. Planting positive affirmations through hypnobreastfeeding into one's subconscious mind, can increase the mother's confidence in breastfeeding so that breastfeeding can be optimal for babies and achieve exclusive breastfeeding